2021
DOI: 10.21601/ijese/11363
|View full text |Cite
|
Sign up to set email alerts
|

Bhutanese Teachers' and Students' Perceptions about Environmental Issues in Bhutan

Abstract: Bhutan aspires to achieve Gross National Happiness (GNH) through sustainable environmental conservation and socioeconomic development. However, the country is facing increasing environmental challenges. Education is considered to be a key component in a range of efforts to remediate current environmental threats in Bhutan. As part of this agenda, the optional school subject of Environmental Science was introduced in 2015 for Classes IX-XII with the aim of equipping young people with the knowledge and values to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…In the case of Bhutan, the whole country is committed to achieving Gross National Happiness (GNH) through sustainable environmental conservation and socioeconomic development; however, the country is facing increasing environmental challenges. Mongar [24] showed that the participants in his study were aware of various environmental problems; however, they lacked knowledge and awareness about climate change issues in Bhutan. Biswas [25] also drew attention to similar problems for the Bangladeshi case.…”
Section: Discussing Lessons Learnedmentioning
confidence: 99%
“…In the case of Bhutan, the whole country is committed to achieving Gross National Happiness (GNH) through sustainable environmental conservation and socioeconomic development; however, the country is facing increasing environmental challenges. Mongar [24] showed that the participants in his study were aware of various environmental problems; however, they lacked knowledge and awareness about climate change issues in Bhutan. Biswas [25] also drew attention to similar problems for the Bangladeshi case.…”
Section: Discussing Lessons Learnedmentioning
confidence: 99%